A New Watermarking Algorithm Based on Visual Cryptography and Secret Sharing for Color Image Authentication and Tamper Detection - Tuncer, Turker; Avcı, Engin (Niyazi ÖZDEMİR, 2017)
Digital forensics is a multi-disciplinary structure that is standardized on the collection, storage, compilation and analysis of evidence, usually obtained as data, through information systems. Digital forensics is not contrary to what is supposed to be a special field, it is a wide field discipline. In this article, a new fragile watermarking method is presented instead of cryptographic hash functions which are frequently used in digital forensics applications. The hash functions cannot detect the region where the attack is made, so we proposed fragile watermarking for authentication in digital data. The best way to make a fragile watermark is to use secret sharing algorithms. In this article, authentication and tamper detection for RGB images are performed using Wu and Chen's visual secret sharing algorithm. The proposed fragile watermarking algorithm is an algorithm with high visual quality, fragile, reliable and high data hiding capacity. Owing to Wu and Chen’s visual secret sharing algorithm, a new fragile watermarking method that is sensitive to angular attacks is proposed.

Adli bilişim, bilişim sistemleri üzerinden genellikle veri olarak elde edilen delillerin toplanması, saklanması, derlenmesi ve analizi konusunda standartları oluşturulan çok disiplinli bir yapıdır. Adli bilişim sanılan aksine özel bir alan değil, geniş alan disiplinidir. Bu makalede adli bilişim uygulamalarında sıklıkla kullanılan özet fonksiyonlarının yerine kırılgan damgaların kullanılması önerilmiştir. Özet fonksiyonları saldırının yapıldığı bölgeyi tespit edemezler bu sebepten dolayı sayısal verilerde kimlik doğrulama için kırılgan damgaların kullanılması önerilmiştir. Bir damgayı kırılgan hale getirebilmenin en iyi yolu sır paylaşım tabanlı algoritmaları kullanmaktır. Bu makalede Wu ve Chen’ in görsel sır paylaşımı algoritması kullanılarak, RGB imgeler için kimlik doğrulama ve saldırı tespiti yapılmıştır. Önerilen kırılgan damgalama algoritması yüksek görsel kaliteye sahip, kırılgan, güvenilir ve yüksek veri gizleme kapasitesine sahip bir algoritmadır. Wu ve Chen görsel sır paylaşımı algoritması sayesinde açısal ataklara karşı hassas, yeni bir kırılgan damgalama sistemi önerilmiştir.
Renkli İmgelerde Kimlik Doğrulaması ve Saldırı Tespiti için Görsel Sır Paylaşım Tabanlı Yeni Bir Kırılgan Damgalama Algoritması
Keywords: Engineering; Mühendislik